Global solutions and decay of a nonlinear coupled system with thermo-elastic - Fuentes Apolaya, Ricardo (2015)
In this present work, the authors prove the existence of global solutions and the decay of nonlinear wave equation with thermo-elastic coupling give by the system of equation…..